1998
DOI: 10.1001/archotol.124.9.985
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction Using Bone Morphogenic Protein in Irradiated Tissue

Abstract: This study supports the potential clinical utility of rBMP-2 and solid hydroxyapatite in irradiated tissue beds. These findings have interesting implications for patients with head and neck cancer who have undergone radiation therapy and need bony reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
0
28
0
1
Order By: Relevance
“…Irradiation of up to 8 Gy did not affect the BMP-2-induced osteoblast differentiation of C2C12 cells in vitro (Ikeda et al, 2000). New bone was formed on BMP-2-treated hydroxyapatite disks implanted into a subperiosteal pocket in rabbits radiated pre-operatively with a fractionated dose of 20 Gy (Howard et al, 1998). Despite these encouraging findings, 3-mm rat calvarial defects preoperatively treated with a 12-Gy radiation dose, and subsequently with BMP-2, had successful bone regeneration, but incomplete healing of the defect (Wurzler et al, 1998).…”
Section: (53) Craniofacial Bone Regeneration After Ablative Cancer Smentioning
confidence: 99%
“…Irradiation of up to 8 Gy did not affect the BMP-2-induced osteoblast differentiation of C2C12 cells in vitro (Ikeda et al, 2000). New bone was formed on BMP-2-treated hydroxyapatite disks implanted into a subperiosteal pocket in rabbits radiated pre-operatively with a fractionated dose of 20 Gy (Howard et al, 1998). Despite these encouraging findings, 3-mm rat calvarial defects preoperatively treated with a 12-Gy radiation dose, and subsequently with BMP-2, had successful bone regeneration, but incomplete healing of the defect (Wurzler et al, 1998).…”
Section: (53) Craniofacial Bone Regeneration After Ablative Cancer Smentioning
confidence: 99%
“…7 It is known that DBM endogenous biological activity is decreased or diminished by heating, 8 chemicals, 9 and radiation. 10 Heat, including autoclaving, not only inactivates the growth factors, but also denatures the supporting collagen structure, and activity can be lost completely after extended heating. 11 It is also known that ethylene oxide, a class I carcinogen, not only reduce bone graft osteoinductivity 12 but also may impose serious health hazards to workers, in addition to being a tedious and time-consuming process.…”
Section: Introductionmentioning
confidence: 99%
“…The specific mechanism behind the osteoinductivity and osteoconductivity of calcium phosphate biomaterials is a continued topic of investigation. Some have suggested that the osteoneogenic potential of such implants is the result of absorption of native bone morphogenic protein (BMP) [14][15][16][17][18]. This absorption is thought to be directly related to the pore size generated in the TCP implants.…”
Section: Discussionmentioning
confidence: 99%